Prospective Memory in Patients with Severe Closed-Head Injury: Role of Concurrent Activity and Encoding Instructions - Giovanni A. Carlesimo; Rita Formisano; Umberto Bivona; Lina Barba; Carlo Caltagirone (Behavioural Neurology)
Objectives: To assess the sensitivity of patients who suffered a severe closed-head injury to the manipulation of attentional resources and encoding instructions during the execution of prospective memory tasks.